The Effects of Teachers' Motivational Strategies on Learners' Motivation: A Controlled Investigation of Second Language Acquisition. Issue 1 (3rd August 2012) - Moskovsky, Christo; Alrabai, Fakieh; Paolini, Stefania; Ratcheva, Silvia
Abstract : While consensus exists about the critical role of learners' motivation in second language acquisition, controlled investigations of the effects of teachers' motivational strategies are limited. The research reported here used a quasi‐experimental design to assess the effects of motivational strategies used by Saudi English as a foreign language (EFL) teachers ( N = 14) on Saudi EFL learners' ( N = 296) self‐reported learning motivation. The experimental treatment involved class‐time exposure to 10 preselected motivational strategies over an 8‐week period; the control group received traditional teaching methods. Multivariate analyses revealed a significant rise in learner motivation over time exclusively or predominantly among experimental vs. control learners, which held robust even when controlling for pretreatment group differences. These results provide compelling evidence that teachers' motivational behaviors cause enhanced motivation in second language learners.